Genotype Base Prevalence of Hepatitis C - Fawad Mahmood, Sumera Kazmi, Hira Wakil, Khalida Kousar, Aamer Ali Khattak, Zahid Ullah Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Hepatitis C virus (HCV) has a positive sense single-stranded enveloped RNA virus. HCV is one of the most common blood-borne diseases causing significant morbidity and mortality globally. HCV causes acute and chronic hepatitis which can eventually lead to permanent liver damage, hepatocellular carcinoma and death. World Health Organization reported that 3 % of the world’s population is suffering from HCV infection that is about 170 million people. The prevalence of chronic HCV infections in Pakistan is about 5%, with very common individuals being infected with HCV genotype 3a prevalence is in the range of 4.1 to 36% reported from various parts of Khyber Pakhtunkhwa Province of Pakistan. This study was carried out in District Mardan Khyber Pakhtunkhwa. A total 1500 HCV suspected individuals visited District Headquarter hospital Mardan during September 2014 to April 2015 were enrolled. HCV antibodies were detected in about 230 patient serums during this screening. Out of these 230 patients 217 patient were further confirmed by qualitative Real Time PCR. All 217 samples were further analyzed for HCV genotyping by PCR based molecular technique. Genotyping results showed that HCV genotype 3a was found in 156 (72%) of the HCV positive isolates, 2a genotype in 22 (10%) and 3b genotype 17 (8%) and remaining 10% were mixed genotype. HCV genotype genotype 3a was declared as the most prevalent genotype with same in both genders that is 72 %. Genotypes 2a, 2b and 3b were more prevalent among male patients while mixed genotype was mostly observed in female infected individuals. Moreover majority of the infected population were form the age group 41-50 year. In 21-30 years age group the most prevalent genotype 3a after than following in competition 3b, in 31-40 years age group 2a 5 (7%), in years age group 41-50 2a 8 (9%) more prevalent. Keywords: Hepatitis C, Genotypes, Pakistan